Analysis of Failed Microvascular Decompression in Patients with Trigeminal Neuralgia - Huang, Zhenyu; Pu, Benfang; Li, Fusheng; Liu, KaiZhang; Hua, Chunhui; Li, Changhua; Zhao, Changyi; Li, Jie; Li, Xinyuan (Journal of Neurological Surgery Part B: Skull Base, 2019)
Background Microvascular decompression (MVD) has been widely accepted as a definitive therapy for primary trigeminal neuralgia (TN). However, some patients may not experience relief of TN symptoms following surgery. In this study, the findings of redo MVD are discussed.Methods Between 2015 and 2017, 205 patients with primary TN underwent MVD surgery in Shanghai Tongren Hospital. Among these patients, 187 had immediate complete relief of symptoms, 8 improved apparently, and 10 reported no symptom relief. Of the 10 patients without relief, 6 underwent reoperation within 5 days, 2 underwent reoperation 3 months after the first procedure, and 2 refused to undergo reoperation.Results The symptoms of those patients who received reoperation disappeared immediately after the surgery. In the second operations, new conflict sites at the motor roots were found in five cases. The real offending vessels were the superior cerebellar artery (SCA) or branch of the SCA in seven cases and the petrosal vein in one case. The nerve was not decompressed completely in either of the two cases. At the 12-month follow-up, no recurrence was found. For the other two patients who did not have reoperation, their symptom persisted. Postoperative complications showed no significant differences between the first and second operations.Conclusion Compression of the motor roots might be one of the causes of TN. Thorough exploration of both sensory and motor roots of the trigeminal nerve is essential to performing a successful MVD operation. Early reoperation for resistant TN after MVD does not increase the incidence of complications.
Keywords: trigeminal neuralgia; microvascular decompression; reoperation; motor root; offending vessel